(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The study aims to evaluate nurses’ practices toward nursing intervention of diagnostic procedures at Neuro Surgical Hospitals, and to find-out the relationship between Nurses’ practices with their Socio-demographic characteristic of age, gender, and education level. A quantitative research approach has been used for this study design starting from December 7th, 2017 to September 2nd, 2019. A purposive sample was adopted including (50) male and female nurses as participants. They were working at Neuro surgical Hospitals. The study Instrument was composed of two Parts: The First Part is concerned with the socio-demographic characteristics, and the second Part includes Nurses’ Practices. Content validity of the instrument was established through a penal of (11) experts. Results have been analyzed through the use of SPSS “Statistical Package for Social Sciences” model 24.0 by using descriptive and inferential statistical methods. Findings of the present study revealed that most of the samples were within the age of (35-44) years who were accounted (34%). The age group of (25-34 years) represent (32%). 24 percent of the study sample were (45-54) years old, and only five nurses were within the age group of (18-24) years old.